A study on the mechanism of vehicle body vibration affecting the dynamic interaction in the pantograph–catenary system. Issue 9 (2nd September 2021) - Yao, Yongming; Zou, Dong; Zhou, Ning; Mei, Guiming; Wang, Jiangwen; Zhang, Weihua
Abstract : A complete track-vehicle-pantograph-catenary (TVPC) coupling dynamics model is presented and several elaborate simulation cases are set to analyse the effect of vehicle body vibration on the pantograph-catenary system (PACS). The catenary is described by a finite-element model while the pantograph, vehicle and track are described by a multi-body model. In addition, different track irregularities are introduced to mimic real track conditions. Through Pearson correlation coefficient and spectrum analysis, the key kinematics parameters are identified, which influence both roof vibration and current collection quality. Frequency response of the TVPC shows that the forces between wheel and rail caused by track irregularities are transmitted to the bogie frame and vehicle body through primary and secondary suspension system, and finally to the PACS. Applying a series of excitation to the pantograph base frame and simulating the interaction between the PACS, the mechanism that the vehicle roof vibration affecting the PACS interaction is verified. Specifically, characteristic frequencies of the vertical displacement of the roof, which are related to the antiresonance and anti-phaseresponse of the pantograph, together with their corresponding amplitudes can be utilised to assess the influence of the body vibration caused by track irregularity on the current collection quality of PACS.